The Challenge of Chemistry Teaching in Transport (Texas Journal of Multidisciplinary Studies, 2022)
This article discusses the importance of chemistry education and chemistry teaching in the field of transport, its goals and objectives. It also discusses the development of a chemistry curriculum in the field of transport, the basic level of learning chemistry as a consistent course in the field of transport, the process of applying chemistry to the field of transport. The article also discusses the fact that a chemistry teacher analyzes the content of the subject in order to provide students with knowledge in the field of transport.